Prediction of Iron Deficiency by Red Cell Distribution Width, Mean Corpuscular Volume and Haemoglobin Concentration in Pregnant Women (BIRDEM Medical Journal, 2019)
Background: Red cell distribution width (RDW) is a routine parameter in fully automated hematology auto analyzer, can give the idea of iron deficiency before haemoglobin and mean corpuscular volume in early iron deficiency or latent stage. Patient can be benefited by doing complete blood count including RDW for the diagnosis of early iron deficiency as a cheaper test than iron profile. This study was aimed to predict early iron deficiency by RDW, mean corpuscular volume and haemoglobin concentration in pregnant women.Methods: In this study, 190 pregnant women were included from Gynae and Obstetric outdoor of Bangabandhu Sheikh Mujib Medical University from august 2008-2009. Complete blood count including haemoglobin percentage, mean corpuscular volume and RDW and iron profile were done. RDW was compared with haemoglobin concentration and mean corpuscular volume in various stages of iron deficiency.Results: RDW was more significant than haemoglobin concentration in latent iron deficiency when haemoglobin level was normal (p